1998
DOI: 10.1046/j.1365-3016.1998.0120s1096.x
|View full text |Cite
|
Sign up to set email alerts
|

Socio‐economic and dietary influences on leg length and trunk length in childhood: a reanalysis of the Carnegie (Boyd Orr) survey of diet and health in prewar Britain (1937–39)

Abstract: Summary. Social class differences in height have been recognised for many centuries. However, few studies have examined the extent to which these differences are made up of differences in leg length or trunk length. This paper reanalyses cross-sectional information on children examined in Britain in the 1930s. We assess associations between socioeconomic status and diet and the components of childhood stature. The analyses were based on the records of 2990 children aged 2 years to 14 years 9 months who were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
100
5

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(114 citation statements)
references
References 19 publications
9
100
5
Order By: Relevance
“…Unlike previous analyses, 15 [23][24][25] we found no evidence that social class differences in height were in greater part attributable to leg length than trunk length. The associations of FEV 1 with leg length were slightly weaker than their relation with trunk length but were stronger than those we found reported in Caerphilly where we used a height adjusted measure of lung function.…”
Section: Main Findingscontrasting
confidence: 99%
“…Unlike previous analyses, 15 [23][24][25] we found no evidence that social class differences in height were in greater part attributable to leg length than trunk length. The associations of FEV 1 with leg length were slightly weaker than their relation with trunk length but were stronger than those we found reported in Caerphilly where we used a height adjusted measure of lung function.…”
Section: Main Findingscontrasting
confidence: 99%
“…In a subset of the Carnegie children (Gunnell et al, 1998a), for whom information at birth was available, similar correlations between birthweight and leg or trunk length were found, suggesting that differences in the components of stature were not related to growth during the gestational period. Results from the Avon Longitudinal Study showed that maternal diet in pregnancy was not associated with height or its components (Leary et al, 2005).…”
Section: Introductionmentioning
confidence: 76%
“…Their results indicate that economic and demographic factors were important influences on the height of children (Gunnell et al, 1998;Martin et al 2002). One of these studies found that that child heights were negatively associated with the number of children in the household but there was no consistent relationship between height and birth order.…”
Section: The Boyd Orr Cohortmentioning
confidence: 99%